Supply chain coordination under budget constraints. (October 2015) - Feng, Xuehao; Moon, Ilkyeong; Ryu, Kwangyeol
Highlights: We study supply chain coordination under budget constraints. We develop a revenue-sharing-and-buy-back (RSBB) contract. The RSBB contract can achieve supply chain coordination under budget constraints. The RSBB contract is more flexible than the revenue-sharing and buy-back contracts. Abstract: Budget constraints are commonly considered in real decision frameworks; however, the literature has rarely addressed the design of contracts for supply chains with budget-constrained members and in which capital costs are considered. In this article, we study supply chain coordination of budget-constrained members when a financial market is unavailable. We propose a revenue-sharing-and-buy-back (RSBB) contract that combines revenue-sharing (RS) and buy-back (BB) contracts. We compare the performance of RS, BB, and RSBB contracts under a coordinated two-stage supply chain in which members experience budget constraints. Results show that the RS and BB contracts are not feasible under certain budget scenarios, whereas the RSBB contract can always be used to coordinate the supply chain and arbitrarily divide profits. We propose a profit allocation approach to address information symmetry created by undisclosed budget thresholds. Our analytical and numerical results provide insight into how managers select an appropriate contract based on their budget scenarios and capital costs.